2010
DOI: 10.1212/wnl.0b013e3181ff966a
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum alkaline phosphatase as a predictor of long-term mortality after stroke

Abstract: Our study demonstrated that increased serum levels of alkaline phosphatase are an independent predictor of all-cause and vascular death after either ischemic or hemorrhagic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 26 publications
4
88
1
Order By: Relevance
“…11 That study examined 2,029 participants with acute stroke and showed that higher ALP was associated with both all-cause mortality and vascular mortality in either ischemic or hemorrhagic stroke. Moreover, Park et al reported that higher ALP was an independent predictor of mortality, MI, and stent thrombosis in 1,636 patients who underwent PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 That study examined 2,029 participants with acute stroke and showed that higher ALP was associated with both all-cause mortality and vascular mortality in either ischemic or hemorrhagic stroke. Moreover, Park et al reported that higher ALP was an independent predictor of mortality, MI, and stent thrombosis in 1,636 patients who underwent PCI.…”
Section: Discussionmentioning
confidence: 99%
“…7-9 Furthermore, higher ALP is related to adverse outcome among survivors of myocardial infarction (MI) 10 or stroke. 11 In a recent study, higher ALP predicted mortality, MI, and stent thrombosis after percutaneous coronary intervention (PCI) with a drug-eluting stent (DES). 12 Considering that vascular calcification hampers the process of re-endothelialization, ALP may contribute to stent thrombosis after PCI whereas coronary artery bypass grafting (CABG) uses the endothelialized vein or artery for the graft.…”
Section: Subjectsmentioning
confidence: 99%
“…We evaluated recurrent vascular events also, apart from mortality, which was not done in the previous study [12]. By this observation, we can derive that serum ALP and phosphate definitely indicate vascular morbidity apart from the other mechanisms mentioned above.…”
Section: Discussionmentioning
confidence: 96%
“…Such studies have been limited in stroke population. One such study was carried out in Korea in patients with stroke [12] to evaluate serum ALP and phosphate as predictors of mortality and recurrent vascular events. It proved that serum ALP and phosphate can be predictor of mortality in stroke, both ischemic and haemorrhagic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation